The achievement of educator and education personnel management in improving the quality of education - Lollita Fristayana; Nisa, Choirun (Journal of Smart Education and Learning, 2025)
The quality of education in Indonesia is currently experiencing a notable decline. According to the latest Program for International Student Assessment (PISA) 2022 results, Indonesia ranks 68th out of 81 participating countries. This study aims to examine the achievement of standard management indicators for educators and education personnel as part of efforts to improve education quality at SDN Mojokerto 3. Employing a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The research instrument consisted of nineteen standard indicators related to educators and education personnel. The study involved teachers and staff at SDN Mojokerto 3 to assess the school’s alignment with the eight national education standards. Findings reveal that several key indicators have not been optimally implemented. Most teachers lack teaching certification, the school does not employ a guidance counselor, administrative head, or librarian, and it lacks both a laboratory and designated laboratory staff.